Structural model equations: Analysis on the performance abilities of the main competencies of graduates - Sunanto, Rahma Faelasofi; Hendrowati, Tri Yuni (Desimal: Jurnal Matematika, 2022)
The purpose of this research is to find out the structural equation model (Structural Equation Model) on the perceptions of users of the graduates of the Teaching and Education Faculty (FKIP) Muhammadiyah Pringsewu University on the performance abilities of graduates' main competencies and the ability to work in teams. This research will use the Partial Least Square (PLS) method which can be used for small samples. In addition, PLS does not require the assumption that the data distribution must be normal or not. The results of this research are ethics, developing English language skills, and self-development has a positive effect on the ability to work in teams and performance skills related to the main competencies of graduates. Also, there is a positive influence from the ability to work on the main competencies, whereby increasing the ability to work will increase the main competencies of FKIP UMPRI graduates.